Design, synthesis, and biological characterization of a potent STAT3 degrader for the treatment of gastric cancer - Li, Haobin; Wang, Lingling; Cao, Fei; Yu, Dehua; Yang, Jing; Yu, Xuefei; Dong, Jinyun; Qin, Jiang-Jiang; Guan, Xiaoqing (Frontiers in Pharmacology, 2022)
Gastric cancer (GC) is one of the main causes of death worldwide, and its occurrence and development mechanism is a complex process involving multiple genes and multiple signals. Signal transducer and activator of transcription 3 (STAT3) has been elucidated as a promising target for developing anticancer drugs in GC. However, there is no FDA-approved STAT3 inhibitor yet. Herein, we report the design and synthesis of a class of STAT3 degraders based on proteolysis-targeting chimeras (PROTACs). We first synthesized an analog of the STAT3 inhibitor S3I-201 as a ligand, using the cereblon (CRBN)/cullin 4A E3 ligase ligand pomalidomide, to synthesize a series of PROTACs. Among them, the potent PROTAC SDL-1 exhibits good anti-gastric cancer cell proliferation activity in vitro, inhibits cell invasion and metastasis, and induces apoptosis in MKN1 cell. Our study shows that SDL-1 may serve as a potential anti-gastric cancer drug, providing ideas for the further development of drugs for clinical use.